MENGISI POLA GAMBAR DENGAN TEKNIK KOLASE MELALUI METODE PEMBERIAN TUGAS PADA PESERTA DIDIK PAUD NEGERI PEMBINA KECAMATAN RENGAT BARAT - Endang Widia (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
In the normal practice of collage, fine motor has not seemed to progress as they only use demonstration method in teaching. Kids less indicates a change in attitude since it tends to be passive and accept what the teacher so that the results obtained are less than the maximum, therefore, the PTK is the writer trying to dig a way to teach learning "fill pattern image with collage technique through the method of administration tasks can improve fine motor learners TK Negeri Pembina Rengat District of West Group B. Lessons built with the creativity of teachers with a suitable method will be able to improve the child's ability. In this PTK in the second cycle of activities "Fill pattern image with collage technique through the method of administration has the task can improve fine motor development of learners group B. It can be caused because the teacher has been creative in the presentation of learning.   Kata Kunci: Pola Gambar, Teknik Kolase, Metode Pemberian Tugas